Venous thromboembolism in primary central nervous system lymphoma during frontline chemoimmunotherapy. Issue 6 (23rd July 2020) - Yuen, Hiu Lam Agnes; Slocombe, Alison; Heron, Vanessa; Chunilal, Sanjeev; Shortt, Jake; Tatarczuch, Maciej; Grigoriadis, George; Patil, Sushrut; Gregory, Gareth P.; Opat, Stephen; Gilbertson, Michael
Abstract: Background: In primary central nervous system lymphoma (PCNSL), venous thromboembolism (VTE) can cause significant morbidity and hinder chemotherapy delivery. Objectives: To assess VTE incidence, timing and adequacy of inpatient and outpatient VTE prophylaxis in patients with PCNSL receiving chemoimmunotherapy with curative intent. Patients/Methods: We reviewed patients diagnosed with PCNSL between 1997 and 2018 who received methotrexate, procarbazine, and vincristine ± Rituximab. Patient demographics, VTE prophylaxis and incidence, adverse events of anticoagulation, and survival outcomes were collected. Results: Fifty‐one PCNSL patients were included (median 67 years [range, 32‐87], 30 males [59%]). Thirteen patients (25%, 95% confidence interval [CI], 14‐40) developed VTE at a median of 1.6 months from diagnosis (range, 0‐4). Patients with Khorana Risk Score ≥2 were more likely to have VTE than those with a KRS < 2 (60% vs 15%; P = .01). Eighty‐five percent had deviations from inpatient VTE prophylaxis guidelines, and outpatient prophylaxis was not routinely administered. Three patients required inferior vena cava filters. Hemorrhagic complications of anticoagulation included an intracranial hemorrhage from therapeutic anticoagulation and three cases of major bleeding from prophylactic anticoagulation. No patients died from VTE or its treatment. Conclusions: Patients with newly diagnosed PCNSL are at high risk of VTE. Further research is required into optimal VTE prophylaxis in PCNSL.